Differential effects of ketoconazole, fluconazole, and itraconazole on the pharmacokinetics of pyrotinib in vitro and in vivo - Wang, Li; Wu, Fan; Xu, Jia; Wang, Yu; Fei, Weidong; Jiang, Hui; Geng, Peiwu; Zhou, Quan; Wang, Shuanghu; Zheng, Yongquan; Deng, Huadong (Frontiers in Pharmacology, 2022)
It has been reported that drug-drug interactions (DDIs) can affect the pharmacokinetics and pharmacodynamics of various oral drugs. To better understand the effects of azole antifungal drugs (ketoconazole, fluconazole, and itraconazole) on pyrotinib’s pharmacokinetics, DDIs between pyrotinib and three azoles were studied with Sprague-Dawley (SD) rat liver microsomes in vitro. Additionally, in vivo pyrotinib metabolic experiment was also performed. Twenty-four male SD rats were randomly divided into four groups: the ketoconazole (40 mg/kg), fluconazole (40 mg/kg), itraconazole (40 mg/kg), and the control group. UPLC-MS/MS was used for the determination of Pyrotinib’s plasma concentration in rats. In vitro experiments showed that IC50 values of ketoconazole, fluconazole and itraconazole were 0.06 μM, 11.55 μM, and 0.27 μM, respectively, indicating that these drugs might reduce the clearance rate of pyrotinib at different degrees. In rat studies, coadministration of pyrotinib with ketoconazole or fluconazole could dramatically increase the Cmax and AUC(0-t) values and decrease the clearance rate of pyrotinib, especially for ketoconazole. However, coadministration with itraconazole had no impact on the pharmacokinetic characters of pyrotinib. These data indicated that ketoconazole and fluconazole could significantly decrease the metabolism of pyrotinib both in vitro and in vivo. More attentions should be paid when pyrotinib is combined with azole antifungal drugs in clinic although further investigation is still required in future.